2012
DOI: 10.1002/nur.21466
|View full text |Cite
|
Sign up to set email alerts
|

A risk to himself: Attitudes toward psychiatric patients and choice of psychosocial strategies among nurses in medical–surgical units

Abstract: Psychiatric patients are liable to stereotyping by healthcare providers. We explored attitudes toward caring for psychiatric patients among 13 nurses working in general hospitals in Ireland. Participants thought aloud in response to a simulated patient case and described a critical incident of a patient for whom they had cared. Two attitudinal orientations were identified that correspond to stereotypical depictions of risk and vulnerability. The nurses described psychosocial care strategies that were pragmatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
16
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 50 publications
1
16
1
Order By: Relevance
“…These risk perceptions were thought to drive a significant label that consumers with mental illness then carried through their generalist admission (MacNeela et al . ). One participant in the Mavundla (, p. 1575) study stated:
… they are noisy at times and cause a problem to other consumers in the ward…others talk in a rude manner, they also shout at us …
…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…These risk perceptions were thought to drive a significant label that consumers with mental illness then carried through their generalist admission (MacNeela et al . ). One participant in the Mavundla (, p. 1575) study stated:
… they are noisy at times and cause a problem to other consumers in the ward…others talk in a rude manner, they also shout at us …
…”
Section: Resultsmentioning
confidence: 97%
“…GHPs suggested that the risk of harm to themselves increases when caring for consumers with mental illness (MacNeela et al . ). Often this risk of harm was related to GHPs’ past negative, personal, and professional experiences of providing care, which leads to some GHPs labelling consumers with mental illness as a safety risk (Reed & Fitzgerald ).…”
Section: Resultsmentioning
confidence: 99%
“…8–10 Students are also taught to look for and recognize potential bio-psychosocial factors that may affect treatment in all of these areas of practice, but they receive minimal training in how to address and accommodate mental health comorbidities. Previous work involving nurses has demonstrated that students and new graduates rely on their own personal experiences and beliefs about people with mental illness to shape their attitudes and guide provision of care; 11 we do not currently know, however, whether the same is true for physiotherapy students and new graduates. Research conducted in Belgium that examined physiotherapy students' attitudes toward psychiatry demonstrated scores deemed to be moderately positive when assessed with the Attitudes Toward Psychiatry–30 items (ATP-30), 12 but little is currently known about Australian physiotherapy students' perceptions and attitudes toward psychiatry and people with mental illness.…”
mentioning
confidence: 97%
“…[13][14][15][16] Even when patients have no comorbid mental health issues, health professionals working in a variety of care settings, including physiotherapists, provide reassurance, psychological support, and education to reduce distress and promote behavioural change. 17 Physiotherapists in Australia are educated and have the skills to manage the physical needs of these patients, and they are trained to look for and recognize potential bio-psychosocial factors that may affect treatment. However, no research has been carried out on how well prepared they perceive themselves to be to manage mental health needs.…”
mentioning
confidence: 99%
“…However, no research has been carried out on how well prepared they perceive themselves to be to manage mental health needs. MacNeela and colleagues 17 highlighted the fact that without adequate training and education in mental health, nurses working in general practice draw on previous experiences and beliefs to provide care for patients with comorbid mental health problems. It would therefore be reasonable to assume that physiotherapists (if reporting the same lack of perceived knowledge, skills, and attributes) may use similar strategies to care for people with mental health problems.…”
mentioning
confidence: 99%